A comparative study of motor ability between elite basketball players from different regions - Vukasevic, V.; Mitrovic, M.; Masanovic, b. (SportMont, 2020)
The purpose of this research was to describe the motor abilities of basketball players from the elite ranking of competition in Montenegro and Serbia, and to make a comparison between them. The sample included 48 participants divided into two sub-samples. The first sub-sample comprised 24 participants who were competing in the First Basketball League of Montenegro and the second sub-sample comprised 24 participants competing in the Serbian Super League. Standardized tests were used to assess motor abilities. For each variable, the central and dispersion parameters were calculated. The differences were determined using a t-test for small independent samples. The results showed that a significant difference was found for distance ball throwing, while no significant difference was present for the remaining variables. Therefore, the results indicate that Montenegrin basketball players have well-developed motor abilities and, in this characteristic, do not lag behind Serbian players.